Tinkerlab : a hands-on guide for little inventors - Doorley, Rachelle, ....- (Boston : Roost Books, 2014)
Probleemoplossend denken - Creativiteit ; kinderen - Knutselen ; kinderen - Design, Build, Concoct, and Discover—55 creative experiments for curious kids! Kids are natural tinkerers. They experiment, explore, test, and play—and learn a great deal in the process through problem-solving and hands-on experiments. From art making to simple robot building, magic potion testing, and nature exploration, this book is about creative experiments, in all fields, that help kids explore the world. Perfect for young children up to age six.